STRATEGY IN IMPLEMENTING CHARACTER BUILDING DURING THE ONLINE LEARNING - Yuliana, Yuliana (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
The COVID-19 pandemic has changed all aspects of life, including the learning system. Learning is done online in most schools. When online learning is implemented, there are difficulties in building the characters of students. This paper aims to describe the strategy in implementing character building during online learning. Method: This paper is a narrative literature review. Articles were searched from Science Direct and Google Scholar. Inclusion criteria were research and review articles. Exclusion criteria were unavailable full-text and not peer-reviewed articles. The results of the literature review revealed that strategy in implementing character building during online learning can be done by implementing open discussion forums and homeroom communication during online learning. Teachers and parents should collaborate to motivate students. OSIS as a student organization can also be used as a special tool for building character among students. In conclusion, building characters need collaboration from students, teachers, and parents. The media can be OSIS, open discussion forum, and homeroom communication.